2021
DOI: 10.1016/j.atmosenv.2020.117975
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mileage on Particle Number Emission Factors for EURO5 and EURO6 Diesel Passenger Cars

Abstract: Air quality is a growing concern worldwide because of its impacts on both the environment and the human health. The road transport sector is a major contributor to this poor air quality. To reduce the emission of particulate matter, all diesel passenger cars were equipped with diesel particulate filters since the EURO5b emission standard. Unfortunately, these filters can be damaged or intentionally removed during the lifetime of a vehicle. This work presents the particle number emission factors for EURO5 and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In the past, the EFs for motor vehicles measured in developed countries were used universally due to the lack of data in developing countries, thus resulting in emission underestimations for on-road motor vehicles . A series of new developments in data collected for emission activity and EFs in recent years, especially those in developing countries, provided valuable inputs for inventory updating. , The most crucial updating included field-measured EFs for residential stoves, newly reported EFs for motor vehicles in developing countries, detailed information on the phase-out of beehive coke ovens in China, new data on residential energy switching and stove upgrading in China and other underdeveloped countries such as India, Mexico, and Nigeria (data were summarized and the statistics derived were applied for other developing countries), , and detailed information on the promotion of end-of-pipe mitigation actions in industry …”
Section: Resultsmentioning
confidence: 99%
“…In the past, the EFs for motor vehicles measured in developed countries were used universally due to the lack of data in developing countries, thus resulting in emission underestimations for on-road motor vehicles . A series of new developments in data collected for emission activity and EFs in recent years, especially those in developing countries, provided valuable inputs for inventory updating. , The most crucial updating included field-measured EFs for residential stoves, newly reported EFs for motor vehicles in developing countries, detailed information on the phase-out of beehive coke ovens in China, new data on residential energy switching and stove upgrading in China and other underdeveloped countries such as India, Mexico, and Nigeria (data were summarized and the statistics derived were applied for other developing countries), , and detailed information on the promotion of end-of-pipe mitigation actions in industry …”
Section: Resultsmentioning
confidence: 99%
“…135,136 Some studies indicated that DPF's PM filtration efficiency increases with increasing filtration time. 137 PAH and soot concentrations in the raw engine exhaust reduced by a greater extent at half load than at full load. 140 A PAH reduction has been reported downstream of the SCR system, especially at high engine loads.…”
Section: Diesel Pm Reduction Overviewmentioning
confidence: 89%
“…135,136 Some studies indicated that DPF’s PM filtration efficiency increases with increasing filtration time. 137…”
Section: Particulate Emissions Overviewmentioning
confidence: 99%
“…22 RDE test cycle in this paper was mainly obtained from a specific cycle performed on road, 23 but it had to be slightly modified to fulfill with the newest regulation. After that, conditions of the cycle have been reproduced in a test bench to eliminate the variations that many parameters as the weather, ambient pressure, 24,25 traffic, driver behavior that produces different dynamic solicitations, 26 road grade, 27 aftertreatment status or vehicle mileage can produce [28][29][30][31][32][33][34] as well as other issues that can appear which can spoil the test like DPF regeneration, traffic jams, etc. For example, different on road cycles that follow the same route, can have a high NOx emission dispersion, 35 and it is likely to find emissions differences of up to 24%.…”
Section: Wltc and Rdementioning
confidence: 99%